A PUZZLE ABOUT NATURALISM - Paseau, A (2010)
This article presents and solves a puzzle about methodological naturalism. Trumping naturalism is the thesis that we must accept p if science sanctions p, and biconditional naturalism the apparently stronger thesis that we must accept p if and only if science sanctions p. The puzzle is generated by an apparently cogent argument to the effect that trumping naturalism is equivalent to biconditional naturalism. It turns out that the argument for this equivalence is subtly question-begging. The article explains this and shows more generally that there are no scientific arguments for biconditional naturalism. © 2010 The Author.